2002
DOI: 10.1093/annonc/13.s1.138
|View full text |Cite
|
Sign up to set email alerts
|

Fertility after treatment for Hodgkin's disease

Abstract: If these preliminary data are consisent in a larger group of patients, GnRH-a co-treatment should be considered in every woman of reproductive age receiving chemotherapy, in addition to assisted reproductive technologies and the investigation into ovarian cryopreservation for future in vitro maturation, autotransplantation or xenotransplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
104
0
13

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 79 publications
4
104
0
13
Order By: Relevance
“…There are several possibilities to preserve future fertility in women exposed to chemotherapy: in vitro fertilization (IVF) and embryo cryopreservation, ovarian tissue cryopreservation, unfertilized ova cryopreservation, and the administration of a gonadotropin-releasing hormone (GnRH) agonist [1][2][3][4][5][6][7]; see Table 1. The possibility of administering an adjuvant treatment that may minimize the gonadal damage caused by an otherwise successful treatment program is obviously very attractive [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are several possibilities to preserve future fertility in women exposed to chemotherapy: in vitro fertilization (IVF) and embryo cryopreservation, ovarian tissue cryopreservation, unfertilized ova cryopreservation, and the administration of a gonadotropin-releasing hormone (GnRH) agonist [1][2][3][4][5][6][7]; see Table 1. The possibility of administering an adjuvant treatment that may minimize the gonadal damage caused by an otherwise successful treatment program is obviously very attractive [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of administering an adjuvant treatment that may minimize the gonadal damage caused by an otherwise successful treatment program is obviously very attractive [1][2][3][4][5][6][7]. Glode et al [8] tested this hypothesis using a murine model and concluded that an agonistic analogue of GnRH appeared to protect male mice from the gonadal damage normally produced by cyclophosphamide [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the quality of tissue harvested does not appear to be adversely affected by patient's age or prior ABVD chemotherapy. As Hodgkin lymphoma (HL) is a common malignancy in young people (Blumenfeld et al, 2002), fertility preservation is an important issue to address when counselling patients prior to chemotherapy. With current regimens of chemotherapy and radiotherapy a large proportion of patients will be cured of their illness, but with the risk of long-term toxicity, particularly with recently developed intensive chemotherapy programmes such as escalated-dose BEACOPP (Bleomycin, Etoposide, Adriamycin s , Cyclophosphamide, Oncovin s , Procarbazine, Prednisolone) (Diehl et al, 2003).…”
mentioning
confidence: 99%